Struktur Naratif dan Nilai Budaya dalam Legenda Asal Usul Orang Basap di Kalimantan Timur: Narrative Structure and Cultural Values in the Legend of the Origin of the Basap People in East Kalimantan - Faradilla, Faradilla; Putri, Nina Queena Hadi (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
Folklore is a culture that is inherited from generation to generation and lives in society. This study aims to analyze the legend of the origin of the Orang Basap as part of oral folklore in East Kalimantan and identify the value of local wisdom contained in it. The method used is descriptive qualitative with a folkloric approach, using the structuralism theory of Vladimir Propp (1968) to analyze the function of figures and the semiotic theory of Roland Barthes (1972) to analyze the meaning of denotative, connotative, and mythical. The research data was in the form of legend texts obtained from the Indonesian Culture website and analyzed using the Miles and Huberman model. The results of the study show that the legend of the origin of the Orang Basap contains a narrative pattern that is in harmony with Propp's morphological theory, with six main narrative functions being found. Semiotic analysis revealed that the symbol of the magic rooster, the ship turned into stone, and the acculturation process contains a deep cultural meaning. This legend also contains three values of local wisdom: social, moral, and belief, which function as a means of character education, social control, and strengthening the cultural identity of the Dayak Basap people.